Association of plant-based food intake in daily diets and hypertension in older adults: a cohort study - Wang, Xiang; Liu, Ting; Shi, Jianbang; Jie, Wei; Dai, Miao (Frontiers in Public Health, 2025)
IntroductionHypertension is a major health concern among older adults, linked to high morbidity and mortality. While plant-based diets may offer health benefits, their association with hypertension in this population remains unclear. This study examines the relationship between plant-based food intake and hypertension incidence in older adults.MethodsWe analyzed data from the Chinese Longitudinal Healthy Longevity Survey, including 3,991 hypertension-free participants aged ≥65 years at baseline (2008). Follow-up was conducted in 2011/2012. Plant-based diet intake was assessed using a plant-based diet index (PDI). Cox proportional hazard models estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for hypertension risk.ResultsDuring a mean follow-up of 3.0 years, 1,764 individuals (44.2%) developed hypertension. Stratified by median PDI, the high PDI group had a 16% lower risk of hypertension versus the control group. Compared to the first quartile of PDI, the highest quartile had a lower risk of hypertension (HR 0.79, 95% CI: 0.69–0.90). The third and second quartiles of PDI had HRs of 0.79 (0.69–0.91) and 0.86 (0.76–0.98), respectively. Subgroup analyses indicated that the relationship between PDI and hypertension risk was not influenced by sex, gender, marital status, living arrangement, economic status, or activities of daily living limitations.DiscussionHigher adherence to a plant-based diet was significantly associated with a reduced risk of hypertension in older adults, suggesting that dietary interventions emphasizing plant-based foods may help mitigate hypertension incidence in this population.